Geochemical bio-signatures in Martian analogue basaltic environments using laboratory experiments and thermochemical modelling - Cogliati, Simone; Wolsey, Elliot; Ramkissoon, Nisha K.; Schwenzer, Susanne P.; Pearson, Victoria K.; Olsson-Francis, Karen (Frontiers in Astronomy and Space Sciences, 2022)
The identification of geochemical bio-signatures is important for assessing whether life existed on early Mars. In this paper, experimental microbiology and thermochemical modelling were combined to identify potential inorganic bio-signatures for life detection on early Mars. An analogue mixed microbial community from an analogue terrestrial fluvio-lacustrine environment similar to an ancient lacustrine system at Gale Crater was used to study microbial dissolution of a basalt regolith simulant and the formation of bio-signatures over a short time frame (1 month) at 14 °C, 2 bar. Microbial growth influenced element dissolution (Mg, Fe, Mn, Ca, K) and the formation of morphologies and Fe-Si amorphous layers on mineral surfaces. Thermochemical models were performed at 14 °C, 2 bar; the results were compared with experimental data to predict bio-signatures that would occur over geological timescales. The pH was varied to simulate abiotic and biotic experimental conditions. Model results suggest that, at water to rock ratios of 100 to 38, a less complex secondary mineral assemblage forms during biotic dissolution compared to abiotic weathering. Carbonates, quartz, pyrite and hydroxyapatite form under biotic conditions, whereas in the abiotic system magnetite and phyllosilicates would also precipitate. These results could be used to distinguish between abiotic and biotic basalt weathering processes, aiding the interpretation of data from Mars exploration missions.